Genetic Alterations of the Thrombopoietin/MPL/JAK2 Axis Impacting Megakaryopoiesis - Plo, Isabelle; Bellanné-Chantelot, Christine; Mosca, Matthieu; Mazzi, Stefania; Marty, Caroline; Vainchenker, William (Frontiers in Endocrinology, 2017)
Megakaryopoiesis is an original and complex cell process that leads to the formation of platelets. The homeostatic production of platelets is mainly regulated and controlled by thrombopoietin (TPO) and the thrombopoietin receptor (MPL)/JAK2 axis. Therefore, any hereditary or acquired abnormality affecting this signaling axis can result in thrombocytosis or thrombocytopenia. Thrombocytosis can be due to genetic alterations that affect either the intrinsic MPL signaling through gain-of-function activity (MPL, JAK2, CALR) and loss-of-function activity of negative regulators (CBL, LNK), or the extrinsic MPL signaling by THPO gain-of-function mutations leading to increased TPO synthesis. Alternatively, thrombocytosis may paradoxically result from mutations of MPL leading to an abnormal MPL trafficking inducing increased TPO levels by alteration of its clearance. In contrast, thrombocytopenia can also result from loss-of-function THPO or MPL mutations, which cause a complete defect in MPL trafficking to the cell membrane, impaired MPL signaling or stability, defects in the TPO/MPL interaction, or an absence of TPO production.